Carbon emission savings and short‐term health care impacts from telemedicine: An evaluation in epilepsy. (31st August 2021) - Blenkinsop, Stephen; Foley, Aideen; Schneider, Natascha; Willis, Joseph; Fowler, Hayley J.; Sisodiya, Sanjay M.
Abstract: Objective: Health systems make a sizeable contribution to national emissions of greenhouse gases that contribute to global climate change. The UK National Health Service is committed to being a net zero emitter by 2040, and a potential contribution to this target could come from reductions in patient travel. Achieving this will require actions at many levels. We sought to determine potential savings and risks over the short term from telemedicine through virtual clinics. Methods: During the severe acute respiratory syndrome coronavirus 2 (SARS‐2‐CoV) pandemic, scheduled face‐to‐face epilepsy clinics at a specialist site were replaced by remote teleclinics. We used a standard methodology applying conversion factors to calculate emissions based on the total saved travel distance. A further conversion factor was used to derive emissions associated with electricity consumption to deliver remote clinics from which net savings could be calculated. Patients' records and clinicians were interrogated to identify any adverse clinical outcomes. Results: We found that enforced telemedicine delivery for over 1200 patients resulted in the saving of 224 000 km of travel with likely avoided emissions in the range of 35 000–40 000 kg carbon dioxide equivalent (CO2 e) over a six and half month period. Emissions arising directly from remote delivery were calculated to be <200 kg CO2 e ( 0.5% of those for travel), representing a significant net reduction of greenhouse gas emissions. Only one direct adverse outcome was identified, with some additional benefits identified anecdotally. Significance: The use of telemedicine can make a contribution toward reduced emissions in the health care sector and, in the delivery of specialized epilepsy services, had minimal adverse clinical outcomes over the short term. However, these outcomes will likely vary with clinic locations, medical specialties and conditions.